Language planning and policy in the Pacific, vol. 1 Fiji, the Philippines and Vanuatu - Baldauf, Richard B. Jr.; Kaplan, Robert B. (Clevedon Multilingual Matters Ltd., 2006)
This volume covers the language situation in Fiji, The Philippines and Vanuatu explaining the linguistic diversity, the historical and political contexts and the current language situation, including language-in-education planning, the role of the media, the role of religion, and the roles of non-indigenous languages. The authors are indigenous and/or have been participants in the language planning context. Fiji and Vanuatu are not well represented in the international language policy/planning literature, while the section on the Philippines draws together the published literature in this area. The purpose of the volumes in this series is to present up-to-date information on polities that are not well-known to researchers in the field. A longer range purpose is to collect comparable information on as many polities as possible in order to facilitate the development of a richer theory to guide language policy and planning in other polities that undertake the development of a national policy on languages. This volume is part of an areal series which is committed to providing descriptions of language planning and policy in countries around the world.
Electronic reproduction.
Keywords: Language planning -- Pacific Area; Language policy -- Pacific Area